Evaluating the Wallet-Based DCEP: Regulatory Innovations and Implementation Strategies in China’s Retail CBDC - Zhenyong Li; Jianxing Li (Laws, 2025)
In pursuit of a higher-quality post-pandemic economic recovery, Chinese authorities have accelerated the development of the e-CNY. This study posits that the e-CNY distinguishes itself from other payment instruments through its controlled anonymity, programmability, and non-interest-bearing attributes. By analyzing patents filed by the Digital Currency Research Institute of the People’s Bank of China between 2016 and 2023, the paper elucidates potential implementation strategies for these distinctive features. The findings suggest that the e-CNY may facilitate a zero-interest accrual model within the prevailing legal framework. Restricted authority access and the anonymity ensured by encrypted data further allow users to maintain a high degree of confidentiality. Additionally, conditional automatic transfers—a prominent function in the e-CNY’s smart contracts—mirror traditional automatic transfers for directed fund utilization without impeding the circulation of fiat currency. The People’s Bank of China has sought to thoughtfully integrate these functionalities into its Central Bank Digital Currency framework, aiming to minimize potential conflicts with existing legal standards. Instead of relying solely on extensive legislative revisions, China’s experience illustrates how deliberate and incremental CBDC design choices can reconcile regulatory compliance with innovative technological advancements.